Updated Standardized Definitions for Efficacy End Points (STEEP) in Adjuvant Breast Cancer Clinical Trials: STEEP Version 2.0. Issue 24 (20th August 2021) - Tolaney, Sara M.; Garrett-Mayer, Elizabeth; White, Julia; Blinder, Victoria S.; Foster, Jared C.; Amiri-Kordestani, Laleh; Hwang, E. Shelley; Bliss, Judith M.; Rakovitch, Eileen; Perlmutter, Jane; Spears, Patricia A.; Frank, Elizabeth; et al.
Abstract : PURPOSE: The Standardized Definitions for Efficacy End Points (STEEP) criteria, established in 2007, provide standardized definitions of adjuvant breast cancer clinical trial end points. Given the evolution of breast cancer clinical trials and improvements in outcomes, a panel of experts reviewed the STEEP criteria to determine whether modifications are needed. METHODS: We conducted systematic searches of ClinicalTrials.gov for adjuvant systemic and local-regional therapy trials for breast cancer to investigate if the primary end points reported met STEEP criteria. On the basis of common STEEP deviations, we performed a series of simulations to evaluate the effect of excluding non–breast cancer deaths and new nonbreast primary cancers from the invasive disease–free survival end point. RESULTS: Among 11 phase III breast cancer trials with primary efficacy end points, three had primary end points that followed STEEP criteria, four used STEEP definitions but not the corresponding end point names, and four used end points that were not included in the original STEEP manuscript. Simulation modeling demonstrated that inclusion of second nonbreast primary cancer can increase the probability of incorrect inferences, can decrease power to detect clinically relevant efficacy effects, and may mask differences in recurrence rates, especially when recurrence rates are low. CONCLUSION: We recommend an additional end point, invasive breast cancer–free survival, which includes all invasive disease–free survival events except second nonbreast primary cancers. This end point should be considered for trials in which the toxicities of agents are well-known and where the risk of second primary cancer is small. Additionally, we provide end point recommendations for local therapy trials, low-risk populations, noninferiority trials, and trials incorporating patient-reported outcomes.